2017
DOI: 10.26753/jikk.v13i2.211
|View full text |Cite
|
Sign up to set email alerts
|

Relaksasi Benson Dan Terapi Murottal Surat Ar-Rahmaan Menurunkan Kadar Glukosa Darah Puasa Pada Penderita Diabetes Melitus Tipe 2 Di Kecamatan Maos

Abstract: Uncontrolled diabetes might generate the physical and psychological complication. The objective of this study was to analyze the effect of Benson’s relaxation and murottal “Ar-Rahmaan” to the fasting blood glucose (FBG) and stress score. This research was quasi experimental study with two group pre test-post test control group design. The research has been done  in the Health Care Center of Maos and “Graha Amanah” Clinic of Maos. Sample technique used total sampling, with 60 according to the inclusion criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 1 publication
0
8
0
2
Order By: Relevance
“…This was in line with the results of other research showing that the most dominant component of distress towards patient distress was an emotional burden distress. [28] The results showed that the indicator value of the emotional burden had lower diabetes distress. Respondents did not feel depressed, had a burden, and felt overwhelmed living with DM, but they could still manage their emotions.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…This was in line with the results of other research showing that the most dominant component of distress towards patient distress was an emotional burden distress. [28] The results showed that the indicator value of the emotional burden had lower diabetes distress. Respondents did not feel depressed, had a burden, and felt overwhelmed living with DM, but they could still manage their emotions.…”
Section: Resultsmentioning
confidence: 95%
“…Moreover, the severity and even the risk of death can trigger an emotional burden on the patient. When patients are unable to manage their emotions, those emotions can be a source of stress which can trigger stress in DM patients [28].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, relaxing conditions provide excellent benefits for stroke patients, because blood pressure will be controlled, and it will eventually improve the neurological problems experienced. Many studies have shown the positive impact of Benson relaxation on anxiety, decreasing pain response, and improving the physiological status of stroke patients (Poorolajal et al, 2017;Purwasih et al, 2017;Rasubala et al, 2017;Ratnawati, 2018;Sahar, 2016).…”
Section: Effect Of Swallowing Exercises and Benson Relaxationmentioning
confidence: 99%
“…Banyak penderita tidak menyadari bahwa mereka telah mengidap diabetes, karena gejalanya memang perlahan sehingga tidak dirasakan (Widyawati, 2010). Berbagai reaksi muncul setelah penderita tahu bahwa mereka mengidap diabetes, mulai dari perasaan takut, cemas, stres, depresi, marah bahkan sampai memberontak (Purwasih, Permana, & Primanda, 2017). Stres yang dialami penderita berkaitan dengan treatment yang harus dijalani seperti diet atau pengaturan makan, kontrol gula darah, konsumsi obat, olahraga dan lain-lain yang harus dilakukan sepanjang hidupnya.…”
Section: Pendahuluanunclassified